Rossetti - Marillier, H. C. (Henry Currie), 1865-1951 (Salt Lake City, UT : Project Gutenberg, 2022)
"Rossetti" by H. C. Marillier is a comprehensive biographical account written in the early 20th century, specifically in the 1900s. The book chronicles the life and works of Dante Gabriel Rossetti, a prominent figure in the Pre-Raphaelite Brotherhood, focusing on both his artistic achievements and personal experiences. The narrative delves into his upbringing, influences, and the key relationships that shaped his career, including his encounters with significant literary and artistic figures of the time. The opening of the book serves as an introduction to Rossetti$1 (Bs background, detailing his Italian heritage and family history. It highlights the impact of his parents on his formative years and his early inclinations toward literature and art. The chapter describes his initial artistic training, collaboration with contemporaries, and the emergence of the Pre-Raphaelite Brotherhood in the mid-19th century. It sets the stage for understanding Rossetti's revolutionary contributions to art and poetry, emphasizing his complex character and the struggles he faced in pursuing his creative ambitions. (This is an automatically generated summary.)s
Release date is 2022-11-07
Al Haines
Keywords: Rossetti, Dante Gabriel, 1828-1882; Pre-Raphaelitism -- Great Britain